Analisis Nisbah Dispersi dan Stabilitas Agregat Tanah pada Penggunaan Lahan SisteM agroforestri di Lahan Miring - Khaerul Umam; I Gusti Made Kusnarta; Mahrup Mahrup (Journal of Soil Quality and Management, 2022)
Agroforestry is a form of conservation principle in maintaining land productivity. The various variations that exist in agroforestry will be able to improve soil physical properties, especially the dispersion ratio and stability of soil aggregates, these physical properties will help in resisting the pressure or force of the falling raindrops. This study aimed to determine the effect of land use by agroforestry systems on the dispersion ratio and stability of soil aggregates on sloping land. The research method used is the descriptive method with sampling done diagonally. There were 3 agroforestry systems (clove-based agroforestry, coffee-based agroforestry, and durian-based agroforestry) which were studied in 3 replications with upstream, middle, and downstream positions. This research was conducted in January-June 2020 in Santoni Village, Kayangan District, North Lombok. Two main parameters were tested, namely the dispersion ratio and the stability of soil aggregates. The results showed that the average value of the ratio of land dispersion indicated by coffee-based agroforestry was 79.85% and the highest was clove-based agroforestry of 91.56%, these values ​​belong to the highly dispersed class. Unlike the case with soil aggregate stability, the highest average soil aggregate stability value was shown in coffee-based agroforestry of 109 and the lowest was clove-based agroforestry of 60. The soil aggregate stability value when interpreted as coffee-based agroforestry was classified as very stable clove-based agroforestry is a relatively stable class. Coffee-based agroforestry is best applied on sloping land so that soil erosion and land productivity can be maintained.